Produtividade, morfogênese e estimativa da temperatura base para genótipos diplóides e tetraplóides de azevém - Medeiros, Liziany Müller (2009)
New genotypes of ryegrass of other localities and with desirable characteristics are being commercialized as tool to reach better zoothenic performance indices. However, research must be carried through on its potentiality in the place to be implanted, searching to prevent problems in the growth and development of these fodder plants, compromising potential biomass yield. Thus, the objectives of this study for the cultivated genotypes of azevém at different times of sowings had been (1) was to estimate lower base temperature, it was also possible to investigate may have seasonal production; (2) to evaluate morphogenetic variables on three types of culms (main culm, first order tiller T1, and first order tiller T2) (3) productivity dry matter seed yield of the ryegrass of dual-purpose submitted. The experimental desing was a split-plot complete randomized block, with four block and treatments arranged in a three-factor (3x2x4) desing: three types of culms (main culm, first order tiller T1, and first order tiller T2), two genotypes (Comum and Advance) and four sowing dates (11/05, 07/06, 05/07 and 09/08/2007). The experimental desing was randomized block, and five ryegrass genotypes: three diploid (Comum, Fepagro São Gabriel, and LE 284 and two tetraploid (Avance and INIA Titán), the combination of number of cuts (from one at four), and five sowing dates (05/11, 06/07, 07/05, 08/09 and 09/01/2007). Values of Tb varied from 7.0 to 8.5ºC for the diploid genotypes and from 9.0 to 10.6ºC for the tetraploid genotypes, depending upon the method. Diploid ryegrass germoplasm have no risk of seasonal decrease in forage production, whereas tetraploids, mainly Avance, may have their growth and development decreased from June to August in Santa Maria because of minimum air temperature. The genotype Advance had the greatest accumulate leaf number and leaf appearance rate and the phyllochron were not different between the two genotypes. Main culm had the greatest leaf or final number and leaf appearance rate and the lowest phyllochron compared to tillers. Later sowing dates led to lower leaf blade elongation rate, final leaf number and leaf appearance rate and greater phyllochron. In all cuts and sowing dates, the leaves proportion was found to be higher in the tetraploids genotypes than in the diploids. The increase of cut number increased total dry matter yield and decreased seed yield, in all sowing dates and genotypes. Generally, the number of spike was small in tetraploids genotypes, bust the length of spike and seed, number and length of seed of spikelets and spacing between spikelets were larger.